Cyclical patterns in profits, provisioning and lending of banks and procyclicality of the new Basel capital requirements - Bikker, Jacob A.; Hu, Haixia (PSL Quarterly Review, 2012)
The proposed risk sensitive minimum requirements of the new Basel capital accord have raised concerns about possible (acceleration of) procyclical behaviour of banking, which might threaten macroeconomic stability. This article analyses the interaction between business cycles and banks over the past two decades for 26 industrial countries. As expected, profits appear to move up and down with the business cycle, allowing for accumulation of capital in boom periods. Provisioning for credit losses rise when the cycle falls, but less so when net income of banks is relatively high, which reduces procyclicality. Lending fluctuates with the business cycle too, but appears to be driven by demand rather than by supply factors such as (shortage of) capital, which contradicts the assumptions underlying capital crunch theory. All in all, over the last decades, distortion caused by procyclical behaviour of banks has been limited, banking crises excepted. JEL Codes: G21, G28, E32